2000
DOI: 10.1021/om000590+
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Chain Structures of Substituted (Dialkylaminomethyl)cyclopentadienyllithium Compounds:  Structural Variations Characterized by Different Involvement of the Internal Amino Donor Ligands in the Solid State

Abstract: Treatment of 6-dimethylaminofulvene (8) with propynyllithium (9a) results in a clean nucleophilic addition at the electrophilic fulvene carbon atom C6 to yield the substituted lithium cyclopentadienide system [C5H4CH(C⋮CCH3)N(CH3)2]Li (10). Likewise, the addition of p-tolyllithium, n-butyllithium, or phenyllithium resulted in the analogous substituted lithium cyclopentadienide systems [C5H4CH(R)N(CH3)2]Li, 11 (R = p-tolyl), 12 (R = C4H9), or 13 (R = Ph), respectively. These four Li−cyclopentadienide systems we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Compounds 9 and 11 represent lithium cyclopentadienyl derivatives with an additional neutral coordination site attached to the Cp fragment. Complexes known in the literature which also belong to this small class of compounds usually form oligomeric structures in the solid state . Thus, a dimeric arrangement as observed in the case of 9 and 11 is unprecedented for such compounds.…”
Section: Resultsmentioning
confidence: 98%
“…Compounds 9 and 11 represent lithium cyclopentadienyl derivatives with an additional neutral coordination site attached to the Cp fragment. Complexes known in the literature which also belong to this small class of compounds usually form oligomeric structures in the solid state . Thus, a dimeric arrangement as observed in the case of 9 and 11 is unprecedented for such compounds.…”
Section: Resultsmentioning
confidence: 98%
“…We had previously shown that 6-dialkylaminofulvenes 3 are readily deprotonated to yield the enamino-substituted Cp-anion equivalents 4 . ,, Treatment of the examples 4b (diethylamino) and 4c (piperidino) with zirconium tetrachloride under carefully controlled reaction conditions gave the bis(enamino-Cp)ZrCl 2 products 5b and 5c , respectively. Their treatment with a Lewis acid (ZrCl 4 ) or a Bro̷nsted acid (R 3 NH + ) catalyst resulted in a rapid intramolecular Mannich-type condensation reaction to yield the unsaturated C 3 -bridged ansa -metallocenes 6b and 6c , respectively (see Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis started from 6‐(dimethylamino)‐6‐methylfulvene 23. Hydride addition gave the Li[C 5 H 4 −CHMe−NMe 2 ] reagent,24 which was then transmetallated with zirconium to yield a meso / rac mixture of [(C 5 H 4 −CHMe−NMe 2 ) 2 ZrCl 2 ] ( 6b ). Methyllithium addition to 6‐(dimethylamino)‐6‐methylfulvene25 gave Li[C 5 H 4 −CMe 2 −NMe 2 ].…”
Section: Resultsmentioning
confidence: 99%